The different amount of composite and amalgam restoration in posterior teeth of patient - Primadisya, Fitri Dwi; Andang, Milly Armilia (Universitas Padjadjaran, 2014)
Introduction: Dental caries is a problem that usually happens in the society. One of the treatments for dental caries is restoration. Dental restoration material which one usually used are compsite and amalgam. The aim of this research is to acknowledge the different amount between the usage of composite and amalgam restoration in posterior teeth of patient in RSKGM Bandung. Methods: Type of research was descriptive. Sample were taken from patients data who had dental treatment of composite and amalgam restoration in posterior teeth in RSKGM Bandung on 1st July – 31st December 2011. Differences result of two restoration inthis research analyzed with test-t analysis.Results: Total amount of posterior teeth restorated was 1485 teeth, which 1445 teeth were restored using composite and 40 teeth were restored using amalgam. It showed that the usage of composite restoration was more than amalgam restoration.Conclusion: there is a significant difference between the number of composite restorations and amalgam on the posterior tooth. The average number of composite restorations is greater than amalgam restoration.